PembuatanPeta Kerja Dalam Rangka Identifikasi Panjang Segmen Batas Kelurahan - Feny Arafah; Adkha Yulianandha Mabrur (Universitas Pendidikan Ganesha, 2023)
A boundary segment is a segment in the form of a boundary line, usually between two adjacent blocks of land. This segment line is important in determining property boundaries and determining land ownership. In the context of mapping, boundary segments are represented as straight lines or a series of straight lines on a map or in spatial databases, and are used to determine the location and extent of property ownership. The boundary segment is very important in determining and ensuring land ownership. Land is an important asset for most people, and boundary segments help define the boundaries of property ownership and ensure that everyone has the appropriate rights to the land they own. Boundary segments are also useful in resolving land ownership issues, such as land conflicts and disputes. Boundary segments help ensure that land occupied or used by a person complies with predetermined boundaries, and helps troubleshoot issues in the event of a dispute. The boundary segment is the part of the boundary of a village that shows the direction and distance between the two boundary points. Boundary segments play an important role in ensuring that the boundaries of a village are clearly defined and not mistaken. This is very important for the context of local administration and governance. According to the reference, boundary segments help in ensuring that specific locations within the sub-district can be correctly identified and ensure that land and other resources are managed efficiently and fairly. In addition, the boundary segment also helps in ensuring that taxes and other burdens are imposed correctly and on the right people. However, many problems occur with boundary segments, such as differences in interpretation of boundaries and lack of available data. Therefore, it is important to ensure that the boundary segments of the village are clearly defined and monitored regularly.